Factors associated with hypertonic dehydration in older Japanese outpatients - Azuna Kinoshita; Takafumi Yonemitsu; Nobuyuki Miyai; Akira Yonemitsu (Journal of General and Family Medicine)
Abstract Background Hypertonic dehydration is common among older adults and is associated with increased mortality and the incidence of several diseases, such as renal failure and cardiovascular complications. Herein, we aimed to statistically identify risk factors for hypertonic dehydration in older adults in Japan. Methods This cross‐sectional study included outpatients aged ≥65 years who visited an internal medicine clinic between March and November 2021. Hypertonic dehydration was determined using serum osmolality (≥300 mOsm/kg) calculated from blood sodium, urea nitrogen, and glucose levels. The body composition of each participant was estimated using bioelectrical impedance analysis. The participants were instructed to record their fluid intake for two consecutive days. We conducted multivariate analysis to examine factors associated with hypertonic dehydration. Results In total, 104 participants (male: 32.7%, mean: 76.6 years) were enrolled. The prevalence of hypertonic dehydration among study participants was 30.8%. After adjusting for potential confounding factors, the daily fluid intake per body weight, body mass index, body fat percentage, diabetes mellitus, and number of medications were significantly associated with hypertonic dehydration. Odds ratios for hypertonic dehydration were 5.47 for daily fluid intake per body weight <20 mL/kg/day (vs. ≥30 mL/kg/day), 2.55 for body mass index ≥25 kg/m2 (vs. <25 kg/m2), and 3.66 for number of medications ≥10 (vs. <6). The area under the receiver operating characteristic curve was 0.712 (95% confidence interval, 0.606–0.817; p = 0.001). Conclusion Decreased fluid intake, obesity, diabetes mellitus, and polypharmacy were independently associated with hypertonic dehydration in older Japanese outpatients.